(untitled) (Cambridge, 2002)
Essays by leading scholars from the U.K., Ireland, France, Germany, Italy, Japan and the U.S. question the effectiveness of the new rhetoric of rights, the contributors examine emerging new approaches at the international, multinational companies
Keywords: Quyền của người lao động,Nhân quyền,Civil rights,Employee rights,Human rights,Quyền công dân